2003
DOI: 10.1093/emboj/cdg127
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase CK2 and protein kinase D are associated with the COP9 signalosome

Abstract: The COP9 signalosome (CSN) puri®ed from human erythrocytes possesses kinase activity that phosphorylates proteins such as c-Jun and p53 with consequence for their ubiquitin (Ub)-dependent degradation. Here we show that protein kinase CK2 (CK2) and protein kinase D (PKD) co-purify with CSN. Immunoprecipitation and far-western blots reveal that CK2 and PKD are in fact associated with CSN. As indicated by electron microscopy with gold-labeled ATP, at least 10% of CSN particles are associated with kinases. Kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
198
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(211 citation statements)
references
References 43 publications
(69 reference statements)
12
198
0
1
Order By: Relevance
“…66 In this work, we also observed that DRB induced a marked decrease of cJun protein level, both in normoxia and in hypoxia (data not shown). Since HIF-1 and AP-1 are known to cooperate to upregulated the expression of several genes in hypoxia, [67][68][69] degradation of c-Jun by DRB may partly explain the decreased VEGF expression in hypoxia.…”
Section: Discussionsupporting
confidence: 56%
“…66 In this work, we also observed that DRB induced a marked decrease of cJun protein level, both in normoxia and in hypoxia (data not shown). Since HIF-1 and AP-1 are known to cooperate to upregulated the expression of several genes in hypoxia, [67][68][69] degradation of c-Jun by DRB may partly explain the decreased VEGF expression in hypoxia.…”
Section: Discussionsupporting
confidence: 56%
“…Aliquots were subjected to SDS-PAGE and Western blotting. The following antibodies were used in this study: anti-CSN1, anti-CSN4, anti-CSN6 and anti-CSN8 antibodies (Biomol), anti-CSN2, anti-CSN3 and anti-CSN7 antibodies [29,30], monoclonal anti-CSN5 antibody (supplied by B. Christy), anti-ubiquitin antibody (FK2, Biomol), anti-USP15 antibody [31], anti-Rbx1 antibody (Rockland), anti-Nedd8 antibody (a gift from C.…”
Section: Cell Culture and Materialsmentioning
confidence: 99%
“…Kinase activity was 6 detected by addition of 0.5 µg recombinant c-Jun and [γ-32 P]-ATP to the pre-incubated CSN complex. Phosphorylation of c-Jun was determined as described previously [30].…”
Section: Csn Activity Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…CSN has an intrinsic isopeptidase activity that deconjugates the ubiquitin-like protein Nedd8/Rub1 from cullin ubiquitin ligases (deneddylation) (Cope and Deshaies 2003). In addition, the complex can associate with protein kinases such as protein kinase CK2 (CK2, formerly casein kinase II), protein kinase D (PKD), and inositol 1,3,4-triphosphate 5/6-kinase (5/6-kinase), which have been shown to phosphorylate c-Jun (Wilson et al, 2001;Uhle et al, 2003). One of CSN subunits, CSN5, also known as Jab1 (c-Jun activation domain binding protein 1), has been identified as a transcription co-activator that enhances transcription activity of c-Jun (Claret et al, 1996) and Myc (Adler et al, 2006).…”
Section: Introductionmentioning
confidence: 99%